PROFESSIONAL WOMEN IN SOUTH AFRICAN PENTECOSTAL CHARISMATIC CHURCHES (Hekima Review, 2010)
This book continues the ever expanding works on Protestantism and economy in its capitalist expression since Marx Waeber’s pioneering idea in this era. In this contribution, the focus is on the South African black women who are climbing the economic ladder in the post apartheid era. The thesis defended is that in the current. setting in South Africa, there is a correlation between protestant church attendance and upward economic mobility for black women population. The reason for this correlation is that the Church provides an indispensible lever that channels the desires and energy of the young upward mobile black women towards economic independence. Specifically, the protestant Church provides the cultural capital that these women need to pursue their dreams.